Brainstem Representation of Auditory Overshoot in Guinea pigs, using Auditory Brainstem Responses - haddadzade niri, hassan; pourbakht, akram; rahbar, nariman; haghani, hamid (Iranian Journal of Child Neurology, 2021)
Objective It is easier for a listener to detect a brief tonal signal presented in a longer masking noise by increasing the delay between the signal and the masker. This phenomenon (overshoot) is influenced by a reduction in cochlear amplification and to date, there is no objective tool to investigate it. Therefore, a different paradigm of the auditory brainstem response (ABR) was utilized to measure auditory overshoot. It was assumed that increasing the delay onset time (DOT) between a signal and a masker reduces the latencies of waves I and III. Materials & Methods Sixteen normal young male guinea pigs were tested. A tone burst stimulus (signal: 16 kHz, 5ms in duration) and wide-band noise (masker: 0.1-8.0 kHz, 100ms in duration) at three DOTs were used. To diminish the effect of the noise on waves, waveforms were subtracted from those derived from the noise burst alone. The absolute latency of the waves I and III, inter-peak latency of the waves I-III, and amplitude ratio of the waves III/I were compared for the 0, 30, and 100ms DOTs and five signal-to-noise ratios. Results The latencies of increased from the 0 to 30ms DOT and then decreased from the 30 to 100ms DOT (p < 0.001). No significant changes were observed in the latency waves at the 100ms DOT compared to the 0ms DOT (p > 0.005). Moreover, there were no significant differences between the three DOTs regarding the inter-peak latency and amplitude ratio of the waves (p <0.005). Conclusion The study results showed an overshoot-like electrophysiological effect using ABR. Therefore, an objective test was used to investigate auditory cochlear gain.